Heart rate and time-motion analyses in top junior players during basketball matches - Karel Hůlka; Roman Cuberek; Jan Bělka (Palacky University, 2013)
BACKGROUND: Basketball performance can be classified as an intermittent physical activity due to the changing situational game conditions and the number of intervening variables. It is necessary to have detailed knowledge about the performance of basketball players during a match as a background for more specific planning of the training process. OBJECTIVE: The aim of this study was to analyse the indicators of internal and external load of basketball player’s performance during a match of U18 top men basketball players as a background for the planning of specific training processes. METHODS: Thirty-two Czech top junior basketball players (male, aged 16.88 ± 0.72 years) participated in this research. The heart rate was recorded and time-motion analysis was conducted during six warm-up matches. RESULTS: The average heart rate was measured to be 167.47 ± 13.01 beats • min.–1, which corresponded to 85.06 ± 6.40% of peak heart rate. The percentages of the total time spent over and under 85% were 63.12% and 36.88%, respectively. Average distance covered was measured to be 5,880.91 ± 831.01 meters. The average work : rest ratio was 1 : 7.95 ± 1.83, ranging from 1 : 4.80 to 1 : 10.92. CONCLUSIONS: The results from these matches suggest that the exercise intensity and sprint activity observed during junior basketball are dependent on the player's position and partly on the level of the performance. The heart rate during a match was not dependent on the positions, however, time-motion analysis revealed significant differences between three basketball positions during a match. The combination of heart rate and time-motion analysis is recommended.